Surface integrity in hot machining of AISI D2 hardened steel - Lajis, Mohd Amri; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul (Trans Tech Publications Ltd., Switzerland, 2012)
This study presents experimental results of machined surface integrity of die material (AISI D2 hardened steel) when hot machining (induction heating) assisted end milling using coated carbide is applied. The aim of this work was to study the influence of induction heating temperature, cutting speed, and feed on the effects induced by hard milling on surface integrity (microhardness and work-hardening). Microhardness was measured to observe the distribution of the hardness beneath the surface and to determine the effect of induction heating on the micro-hardness distribution and work-hardening phenomena. The behaviour of microhardness induced in the subsurface region when end milling under room and induction heating cutting conditions using coated carbide inserts was also investigated. The surface integrity and subsurface alteration have been investigated by employing scanning electron microscope (SEM) and Vickers microhardness tester.